Analisis Kinerja Keuangan Perusahaan Multinasional: Perbandingan Rasio Keuangan dalam Konteks Global - Budiandru; Karsam; Zakkiandri (Owner : Riset dan Jurnal Akuntansi, 2023)
Motivated by the need to analyze the financial performance of multinational enterprise to support effective decision-making in managing and investing in multinational businesses. The problem is the lack of comprehensive and detailed financial performance analysis for multinational companies, which hinders effective decision-making in managing and investing in multinational businesses. The objective is computing the financial performance of multinational enterprise with financial ratios as analysis variables. Financial data from a number of multinational companies operating during a specific period were collected and analyzed. Financial ratios we need include Current Ratio, Quick Ratio, Debt to Equity Ratio, and Debt to Assets Ratio. Through descriptive analysis, we know about liquidity level of multinational companies is relatively stable with small variations in the Current Ratio. However, a lower liquidity level is observed in the Quick Ratio. Furthermore, ANOVA analysis revealing the significantly different between multinational companies in all observed financial performance variables. General Linear Model was used to analyze significant differences in dependent variables among groups of multinational companies. The findings of this research indicate significant variations in the financial performance of multinational enterprise based on these variables. Kruskal-Wallis analysis shows significant differences between treatment groups. The filnal results providing the better understanding of the financial performance of multinational companies and can serve as a basis for practitioners and decision-makers.